Pengembangan e-learning mata pelajaran geografi untuk meningkatkan hasil belajar peserta didik kelas X SMA - Imam Widodo; Mukminan Mukminan (Universitas Negeri Yogyakarta, 2018)
Penelitian ini bertujuan untuk: (1) menghasilkan produk e-learning pada mata pelajaran Geografi bagi peserta didik kelas X SMA, (2) mengetahui kelayakan produk e-learning menurut ahli materi dan ahli media, (3) mengetahui respon peserta didik sebagai pengguna e-learning, (4) mengetahui keefektifan e-learning mata pelajaran Geografi terhadap hasil belajar kognitif peserta didik kelas X SMA, dan (5) mengetahui keefektifan e-learning mata pelajaran Geografi terhadap hasil belajar afektif khususnya kemandirian belajar peserta didik kelas X. Penelitian pengembangan ini mengacu langkah yang dikembangkan oleh Alessi Trollip. Prosedur pengembangan meliputi tahap perencanaan, desain, dan pengembangan. Tes beta yang dilakukan terhadap 32 peserta didik kelas X1 sebagai calon pengguna sekaligus sebagai kelas eksperimen, dan sebagai kelas kontrol X2 sebanyak 21 peserta didik. Pengumpulan data dilakukan menggunakan lembar validasi, angket kemandirian belajar, angket respon peserta didik, dan tes hasil belajar. Hasil penelitian menunjukan: Kelayakan produk e-learning masuk dalam kriteria sangat baik. Terdapat perbedaan hasil belajar antara kelas eksperimen dan kelas kontrol setelah pembelajaran. Rerata N-gain kelas eksperimen lebih tinggi dibandingkan dengan kelas kontrol. Terdapat perbedaan kemandirian belajar antara kelas eksperimen dan kelas kontrol setelah pembelajaran. Rerata N-gain kelas eksperimen lebih tinggi dibandingkan dengan kelas kontrol.Kata Kunci: e-learning, geografi, hasil belajar, kemandirian belajar DEVELOPING E-LEARNING OF GEOGRAPHY LESSON TO INCREASE LEARNING ACHIEVEMENT OF 10th GRADE STUDENTS OF SENIOR HIGH SCHOOLAbstractThis research aims to: (1) produce e-learning geography lesson for 10th grade students of Senior High School, (2) determine the feasibility of e-learning products according to subject matter experts and media experts, (3) determine the response of the learner as users of e-learning, (4) determine the effectiveness of e-learning in the subject of Geography on the cognitive learning achievement for 10th grade students of Senior High School, and (5) determine the effectiveness of e-learning in the subject of geography to the affective learning in particular the self-regulated learning for 10th grade students of Senior High School. This research is a research and development (R D) and adapted from the model of Alessi Trollip. The procedure includes the development of the planning, design, and development. Beta test which was conducted to 32 students class X1 as prospective users, as well as the experimental class and control class X2 as many as 21 students. Collecting data used validation sheet, questionnaire self-regulated learning, the questionnaire of student’s responses, and achievement test. The results of the study are: The feasibility of e-learning products is included in very good criteria. There are differences in learning achievement between the experimental class and control class after learning. The mean N-gain of the experimental class is higher than that of the control class. There are differences in self-regulated learning between the experimental class and control class after learning. The mean N-gain experimental class is higher than that of the control class.Keywords: e-learning, geography, learning achievement, self-regulated learning.